Phenomenology and Existentialism - Lee, Edward N.; Mandelbaum, Maurice (Johns Hopkins University Press, 2020)
Originally published in 1967. Focusing on key philosophers and the tenants of their thought, Phenomenology and Existentialism forms a wide-ranging introduction to two important movements in modern philosophy. Included are essays by Roderick M. Chisholm on Brentano, Aron Gurwitsch on Husserl, E.F. Kaelin on Heidegger, J. Glenn Gray on Heidegger, George L. Kline on Hegel and Marx, James M. Edie on Sartre, Frederick A. Olafson on Merleau-Ponty,Herbert Spiegelberg on Phenomenology and psychology, and Albert William Levi on the alienation of man.